Rancang Bangun Antena Mikrostrip Meander-line 915 MHz untuk Optimasi Jarak Pengiriman Data Alat Ukur pH Meter Sistem Telemetri - Widya Cahyadi; Ardiansyah Ardiansyah (Universitas Syiah Kuala, 2017)
In recent years the use of wireless technology is growing rapidly. Not only limited to the use of cell phones but also other wireless devices that use the air media as the information transmission line. The antenna is a very important component in wireless devices because its function is to convert electrical signals into electromagnetic signals and vice versa on transmitting the information in the air. One of the technologies that can overcome this is the use of microstrip antennas. The microstrip antenna is a lightweight, easy to fabricate so that can be placed on almost any type of surface and small size compared to other types of antennas. Because of its properties, microstrip antennas are highly suited to current needs. This antenna can be integrated with other telecommunications equipment in small size. This paper describes the design and realization of microstrip meander-line antenna at working frequency 915 MHz to be integrated on a telemetry measuring device pH meter water. The integration of the meander-line microstrip antenna on the pH meter measurements is capable of transmitting pH data at unobstructed conditions with a maximum distance of 210 meters, and in a blocked condition, a building is capable of transmitting pH data with a maximum distance of 110 meters.